Menjerat Overclaim: Tanggung Jawab Hukum Pelaku Usaha Skincare dalam Perspektif Perlindungan Konsumen - Regita Surya Prameswari; Ahmad Irzal Fardiansyah; Fristia Berdian Tamza (CV Rewang Rencang, 2025)
The skincare industry in Indonesia has experienced rapid growth in recent years, leading businesses to innovate their beauty products and then promote or advertise them. However, many businesses are currently making exaggerated claims when promoting their products, and some even have products whose contents do not match their labels or promotional claims, causing consumers to suffer losses. The problem addressed in this study is how to regulate overclaiming and product inconsistencies based on the Consumer Protection Law and how to hold business actors accountable for such violations. The method used is normative legal research with a qualitative approach, based on the search and analysis of primary, secondary, and tertiary legal materials, which include legislation (particularly the UUPK and BPOM regulations in the field of cosmetics), legal literature, scientific journals, and other relevant sources. The results of the study show that the practice of overclaiming and product content inconsistencies in skincare products constitute violations of basic consumer rights, particularly the right to safety and the right to accurate, clear, and honest information. In the event of a violation, business actors can be held civilly liable through compensation obligations as stipulated in Article 19 of the UUPK, or criminally liable through the threat of sanctions under Article 62 in conjunction with Article 8 of the UUPK. The research findings also confirm that BPOM supervision and test results play a strategic role as the basis for law enforcement against business actors. Therefore, administrative, civil, and criminal sanctions are expected to have a deterrent effect and strengthen consumer protection in the skincare industry.